Nondestructive Determination of Sweetness of Orange Juice using Portable Near Infrared Spectroscopy - Jha, S N (Journal of Agricultural Engineering, 2007)
A simple and nondestructive method using portable near infrared spectroscopy (NIRS) was investigated to determine the total soluble solids (TSS) of orange juice. Juice from 110 orange was squeezed and their spectra in the range of 311.7 - 1124.8 nm wavelength were acquired using a portable Vis-NIR spectrometer and fibre optics as light transmitting medium. Sweetness in terms of total soluble solids contents of juice was determined using a digital refractometer. Whole samples were divided into two sets: calibration and validation; and partial least squares regression of spectral data in wavelength region from 703.3 to 1124.8 nm was performed. The standard errors of calibration and validation were found to be 0.47degree and 0.41degree Brix, respectively, which are reasonably low. It indicates that sweetness of juice may be determined nondestructively using a portable NIR spectrometer without sacrificing accuracy as compared to that by a refractometer.